단계별 질문 중심의 단원 설계가 초등학생의 '계절의 변화' 개념 이해에 미치는 효과 - 노자헌; 손준호; 정지현; 송진여; 김종희; Noh, Ja-Heon; Son, Jun-Ho; Jeong, Ji-Hyun; Song, Jin-Yeo; Kim, Jong-Hee (대한지구과학교육학회지, 2019)
The purpose of this study is to find out the effects of reconstructing unit 'Seasonal Change' using step-by-step questioning for concepts changes to adjusting misconceptions of elementary school students. Most students have pre-conceptions at describing seasonal changes based on their experiences. Therefore, in newly developed unit, we reconstructed unit to include core teaching and learning contents by finding out common pre-conceptions of students and specifying purpose of teaching at misconceptions found in pre-conceptions as 'constituent of class for conceptual change'. After the scientific concept test, the result of 24 students in experimental group is statistically significant. Also, according to the result of qualitative analysis, the number of activated conceptional resources and degree of specificity in explaining seasonal changes are higher than that of control group. 이 연구의 목적은 단계별 질문을 활용해 '계절의 변화' 단원을 재구성함으로써 학생들의 오개념 변화에 어떠한 효과가 있는지 확인해 보고자 한 것이다. 대부분의 학생들은 계절 변화의 원인을 설명하는데 자신의 경험을 바탕으로 하여 선개념을 구성하고 있었다. 그래서 개발한 수업에서는 학생들이 갖고 있는 선개념 중 오개념을 조사하고 이에 대한 지도 계획을 '개념 변화를 위한 수업 설계 요소'로 명시하여 핵심 교수 학습 내용이 되도록 단원을 재구성하였다. 연구 결과, 실험 집단의 24명 학생들을 대상으로 과학 개념 검사를 실시하여 통계적으로 유의미한 효과가 있음을 알 수 있었다. 또한 질적 분석을 실시한 결과, 계절 변화를 설명할 때 활성화한 개념적 자원의 수와 계절 변화를 설명하는 구체성의 정도가 비교 집단에 비해 높음을 확인할 수 있었다.